2022
DOI: 10.1108/jfmm-10-2021-0269
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of clothing design factors: how to attract consumers' visual attention and enhance emotional experience

Abstract: PurposeThis paper aims to study consumers’ visual attention and emotional experience with clothing design factors and their combinations from the perspective of cognition and emotion and propose an interaction phenomenon to evaluate the combined effect of clothing factors to better guide online clothing design and sales.Design/methodology/approachAn eye movement physiology experiment was conducted, 33 participants screened by questionnaires were invited for this experiment. Hypotheses of visual attention were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…As can be known from E1(b) data, a poor visual experience in clothing affects the entire online shopping experience, and consumers do not develop a good emotional experience even under the stimuli of “sight + touch.” As shown in the combined E1(a) and E1(b) data, there is a significant difference between the good and bad visual experience of clothing in tactile attributes of online purchases. Furthermore, it was found in the interviews following the experiment that the subjects generally responded that the overall matching of the sweater was very helpful for forming mental imagery and had produced excellent emotional experience, which is consistent with the findings by Mo et al (2022).…”
Section: Discussionsupporting
confidence: 84%
“…As can be known from E1(b) data, a poor visual experience in clothing affects the entire online shopping experience, and consumers do not develop a good emotional experience even under the stimuli of “sight + touch.” As shown in the combined E1(a) and E1(b) data, there is a significant difference between the good and bad visual experience of clothing in tactile attributes of online purchases. Furthermore, it was found in the interviews following the experiment that the subjects generally responded that the overall matching of the sweater was very helpful for forming mental imagery and had produced excellent emotional experience, which is consistent with the findings by Mo et al (2022).…”
Section: Discussionsupporting
confidence: 84%
“…Findings also confirmed that customers are attracted to distinctive, appealing designs, and often choose items that stand out. Design uniqueness significantly affects consumer interest and buying intentions, with a clear preference for individuality in fashion (Mo et al, 2023;Lang & Wei, 2019). The findings are corroborated by the outcomes of the interviews below.…”
Section: Customers Pains and Gainssupporting
confidence: 57%
“…However, although the questionnaire data can assist us in determining the positive and negative emotions based on the multi-channel physiometer indicator, there are still some inconsistencies between the questionnaire data and the multi-channel physiometer data in the experiment, so it deserves further study. A good option is the association of polysomnography with other physiological experiments, for example, pupil size indicator based on eye-tracking equipment are widely used for emotion research (Mo et al, 2022; Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Saintives (2020) discovered that there is still a lack of research on consumer emotions in online shopping, pointing out that most of the studies in this field still rely on the S-O-R model, this paper also used the S-O-R model as the theoretical framework for this study. In addition, multiple studies have revealed that the emotions of online shopping are different from those of in-store shopping (Brunner-Sperdin et al, 2014; Mo et al, 2022; Tupikovskaja-Omovie & Tyler, 2020; Yin et al, 2013). The research by Hult et al (2019) also supports the interaction between online and offline shopping and customer perceived value, which also affects consumer satisfaction.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%